Objektifikasi Qisas Dan Diyat: Sebuah Tawaran Pembaharuan KUHP - Sulaiman, Akhmad; Ikhlas, Nur (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2018)
The reporting media indicates that the killing ceses in Indonesia keep on rise. It means that applying killing criminal law that refers to KUHP is not effective. This condition requires KUHP reforming because the right of human life must be vouched by the government. The criminal law of Indonesia must punish a killer more forceful. The writers offer qisas and diyat to be applied in Indonesia but they have to pass through objectification. According to Kuntowijoyo, objectification is interpreting religion's internal doctrines into objective categories in order to be able to be applied, actualized, and accepted by moslem and nonmoslem. It is research and development that strives for developing Kuntowijoyo's objectification on KUHP reforming. With changing qisas term into die punishment, diyat into compensation for victim's family, and adjusting with objective condition in Indonesia, qisas and diyat will be accepted by every national of Indonesia and become solution of criminal law of Indonesia that is not effective.